ANALISIS RISIKO BENCANA GEMPABUMI DI WILAYAH NUSA TENGGARA BARAT - Adi Kurniawan, Melki; Suarbawa, Komang Ngurah; Septiadhi, Ardhianto (BULETIN FISIKA; Vol 18 No 1 (2017): BULETIN FISIKA, 2017)
An investigation of risk identification earthquake disaster in Nusa Tenggara Barat by three factors: the danger factor of earthquakes is Peak Ground Acceleration(PGA), vulnerability factor is population density by district, as well as the capasity factors are HDI (Human Development Index) by district in the province of West Nusa Tenggara has be done. PGA value calculation was performed using the attenuation function Fukushima and Tanaka with earthquake parameter data from 1970 - 2014 with the criteria of magnitude ? 4.5mB, depth ? 60 km and the epicenter in the range of 7.5 o - 12 o and 115 o -120 o BT and  for disaster risk index calculation earthquake using AHP (Analytical Hierarchy Process). From the calculation of the obtained regions with earthquake disaster risk levels are highest are southern Dompu, Mataram, Bima, northern Bima Regency while the lowest West Sumbawa regency and southern Sumbawa regency.